Mobilization of blood-derived stem and progenitor cells in normal subjects by granulocyte-macrophage- and granulocyte-colony-stimulating factors - Lane, Thomas A.; Ho, Anthony Dick; Bashey, Asad; Peterson, Sandra; Young, Dennis; Law, Ping (Transfusion, 1999)
BACKGROUND: It was previously reported that the combination of granulocyte-macrophage-colony-stimulating factor (GM-CSF) and granulocyte-CSF (G-CSF) for 4 days mobilized more primitive CD34+ subsets than did either G-CSF or GM-CSF alone. STUDY DESIGN AND METHODS: The studies determine the optimal number of days of growth factor dosing for mobilization and collection of peripheral blood progenitor cells, by increasing the days of administration of GM-CSF and/or G-CSF or employing the sequential administration of GM-CSF followed by G-CSF. Sixty normal subjects were given injections of G-CSF or GM-CSF alone; GM-CSF and G-CSF concurrently for 4, 5, or 6 days; or a sequential regimen of GM-CSF for 3 or 4 days followed by G-CSF for 2 or 3 days. A 10-L apheresis was performed 24 hours after the last dose. RESULTS: The three most efficacious mobilization regimens consisted of sequential GM-CSF for 3 days followed by G-CSF for either 2 or 3 days and G-CSF alone for 5 days. Each of these regimens resulted in the collection of significantly greater numbers of CD34+ cells by apheresis than any of the 4-day dosing regimens with G-CSF and/or GM-CSF (sequential GM-CSF/G-CSF: 3 days/2 days = 3.58 ± 0.53 × 106 CD34+ cells/kg; GM-CSF/G-CSF: 3 days/3 days = 4.45 ± 1.08 × 106 CD34+ cells/kg; G-CSF: 5 days = 3.58 ± 0.97 × 106 CD34+ cells/kg; all p < 0.05 vs. G-CSF and/or GM-CSF for 4 days). Clonogenic assays generally paralleled the level of CD34+ cells. Regimens containing GM-CSF resulted in a higher percentage of the cells from primitive CD34+/CD38-/HLA-DR+ subset than G-CSF alone. CONCLUSION: Compared with 4-day dosing regimens with G-CSF and/or GM-CSF, mobilization of CD34+ cells in normal subjects using sequential GM-CSF for 3 days followed by G-CSF for 2 or 3 days or using G-CSF alone for 5 days increased the number CD34+ cells that can be collected by a single 10-L apheresis 24 hours after the last dose of cytokine.
Elektronische Reproduktion der Druckausgabe
Gesehen am 14.12.2021